(untitled) (Vietnam Journal of Community Medicine, 2026)
SPACE TUMORS Objective: To evaluate the outcomes of endoscopy-assisted transoral resection of parapharyngeal space tumors. Methods: A scoping review. A literature search was conducted to identify, screen, and analyze relevant studies. Selected articles were synthesized to assess the effectiveness of endoscopy-assisted transoral resection of parapharyngeal space tumors. Results: Twelve studies published between 2015 and 2026 were included. Among them, eleven were retrospective studies, one was a prospective study. Endoscopy-assisted transoral resection of parapharyngeal space tumors has shown the potential for complete tumor removal and low recurrence risk. Comparing to the external approach, endoscopy-assisted transoral resection tend to have: lower complication rates, shorter surgical time, less blood loss, reduced hospital stay, less pain experience, and better cosmetic results. Conclusion: Endoscopy-assisted transoral resection of parapharyngeal space tumors is a safe and promising results method. This surgical approach ensures successful tumor treatment while reducing the complication rate and improving aesthetic factors compared to lateral cervical approach.